Role of cell division in differentiation of myoblasts infected with a temperature-sensitive mutant of Rous sarcoma virus. - Falcone, G (1984)
The relationship between a potential requirement for cell DNA synthesis and the expression of differentiated muscle cell functions was investigated using primary chicken embryo myoblasts infected with a temperature-sensitive mutant of Rous sarcoma virus (RSV). Under optimized conditions, transformed myoblasts growing at the permissive temperature could differentiate into multinucleated myotubes, express muscle-specific myosin, desmin and acetylcholine receptors in the absence of DNA synthesis and cell division following a shift to the non-permissive temperature. Furthermore, the experiments demonstrate that individual RSV-infected myoblasts have two options: either to divide and express the transformed phenotype or to withdraw from the cell cycle and differentiate into myotubes. The choice between these options appears to depend on the protein-kinase activity of pp60src, the src gene product.